Seasonal influences on ungulate movement within a fenced South African reserve - O'Kane, C; Macdonald, D (Cambridge University Press, 2018)
The movement of African ungulates between habitats is determined by diverse factors including forage composition, availability and quality, water availability, topography, the catenary level and the effect of fire on vegetation. We assessed how grass flushes, following dry-season fires, and availability of water influenced seasonal movements of hartebeest, impala, warthog, white rhino, wildebeest and zebra in Ithala Game Reserve, a fenced reserve in South Africa. Over a 6-d period each month for 4 y, road transects covering a representative sample of the reserve’s different vegetation types, and 23% of the reserve’s total area, were carried out. We recorded the species, number, sex and age class of herbivores, obtaining 8742 records (total herbivores sighted = 47,055), and obtained positional data on sightings over the last 2 y of the study. Using a GIS-based approach, we determined that ruminant, but not non-ruminants, were significantly attracted to dry-season grass flushes, and that presence or absence of such flushes significantly affected their mean distance to water and hence seasonal movements on the catena.